Duodenal perforation: role of multi detector computed tomography (MDCT) - Suthar, Pokhraj Prakashchandra; Pandey, Gaurav; Patel, Jigar J.; Doshi, Rajkumar Prakashbhai (International Journal of Research in Medical Sciences, 2017)
Perforation of peptic ulcers, more specifically; ulcers of the first part of the duodenum carry mortality up to 11 %, with a higher mortality seen in patients over the age of 50 years. Main symptoms are acute onset abdominal pain and vomiting. Guarding & rigidity is present on examination. Conventional X-ray abdomen standing is the first investigation, which shows free gas under diaphragm. MDCT scan is required for identifying the presence, site and cause of gastrointestinal tract perforation. Early diagnosis and treatment is mandatory as it is a grave emergency condition.